Quality of drugs and drug use patterns at different level of health care settings in Nepal, 2016. (2017)
SUMMARY: Background: Drug quality has direct impact on patient's health. The drug should be of standard quality in order to meet its therapeutic efficacy. The poor quality of drug results negligible to detrimental effect on human's health. Burgeoning various health issues and dampening medicine efficacy has questioned whether the drug being administered is appropriate and of standard quality in every individuals. In addition to quality of drug, rising cases of irrational use of the drugs and lack of patient compliance are other key factors which directly contribute in diminishing drug efficacy. This study aims to assess the quality of drug and drug use pattern at different level of health settings in Nepal. Method: It was a descriptive cross sectional study. Out of the total listed health facilities from 5 developmental regions, 90 health facilities (1 District Hospital, 1 Primary Health Care Centre, 4 Health Posts from each district) representing three geographical areas from each developmental region was chosen randomly. Thirty patients from each selected Health Post and Primary Health Care Centre and 50 patients from each District Hospital were identified prospectively. To assess prescribing and dispensing practice of the drug, exit client interview was taken with individual patient from each selected health facility. In order to analyze the quality of drug, 10 generic medicines, each of 5 different brands were collected randomly from three private licensed pharmacies nearest to each selected government facilities. Also, free essential drugs supplied by the Government of Nepal was collected on the scientific basis i.e. Biopharmaceuticals Classification System IV (BCS-IV) drugs, frequency of prescription, therapeutic category from selected districts. Similarly, face to face interview was also taken with health facility in-charge of selected health facility using structured questionnaire and required data were collected to determine the storage condition of the drug. Data were entered and managed in Epidata, further cleaned on Microsoft excel 2007 and analyzed using the SPSS version 20. Descriptive analysis was presented on number and percentage in tabular form. Written informed consent was taken from each patient and for children less than 14 years consents were taken from their parents. Results: Among total prescribed drugs from all health facilities, 60.71 % of drugs were found to have been prescribed with generic names and highest percentage were reported from District Hospitals. Next, among total prescribed drugs 68.91% were found to be essential drug while 23.74 % of drugs were found to be antibiotics. Out of total drugs that were dispensed from each health facilities, only 51.81 % of drugs were found to have been dispensed in sufficient quantity. And among those patients, who were dispensed medicines only 49% were found to have complete knowledge about medicine and its use. Further, there was no implementation of standard measures for storage of drugs in health facilities. Also, 26 % of health posts were found not storing vaccines in cold chain. Among total drugs sent for in-vitro analysis in two laboratories, Paracetamol 500 mg BP (Cetophen) supplied as essential drug by Government of Nepal was found substandard. Further, other eight drugs including two essential drugs supplied by Government of Nepal (GoN) and six non-essential drugs supplied from private sectors failed to meet required standard in one laboratory. Similarly, large variations in price were reported among different brands of same generic medicines. There were almost 400 % variations in price among different brands of Tamsulosin 0.4 mg capsule, Cefixime 200 mg Tablets and Amlodipine 5mg Tablets. Conclusions: Drugs are prescribed with generic names from majority of health facilities especially by District Hospitals. Only half of the patients are dispensed complete prescribed medicines and among those who are dispensed medicines, majority lack complete knowledge regarding medicine use. Similarly, some of the drugs are found to be substandard in Nepalese market. The widely used drug Paracetamol 500 mg BP (Cetophen) supplied as essential medicine by GoN is found substandard. In addition to this, other eight drugs including two essential drugs supplied by GoN and six non-essential drugs supplied by private sectors are also found substandard. Similarly, there are large variations in price among drugs of different brands of same generic. Few variations can also be seen in terms of expiry date. Health facilities have not fulfilled all the criteria of standard storage system of drugs. In addition, few health posts do not even store vaccines in cold chain.